THE EFFECT OF NANO ZnO MORPHOLOGY ON STRUCTURE, DIELECTRIC CONSTANT, AND DISSIPATION FACTOR OF CA-NANO ZnO/ITO FILMS - Mustikasari, Ayu Azrurin; Diantoro, Markus; Mufti, Nandang; Suryana, Risa (Jurnal Neutrino, 2018)
Research to utilize natural polymers continues to be driven primarily by utilization as an environmental friendly energy-generating and storage material. The high porosity makes cellulose acetate (CA) a good candidate as a dielectric material as the basis of the supercapacitor device. Various dopants and compositions have been widely used, but the nano size morphological differences of the same material are rarely reported. Two types of ZnO are prepared, i.e., nanoparticles and nanorods deposited with CA and deposited on ITO glass substrate. The CA-ZnO / ITO composite film was fabricated through spin coating technique. This study focused on ZnO morphological difference on the microstructure and the dielectricity of CA-ZnO /ITO composite films. The morphology of nanoparticles and nanorods of ZnO were analyzed more detail with respect to its microstructure and dielectric properties. It is revealed that the change of ZnO morphology from nanoparticles to nanorod increase the capacitance and dielectric constant significantly from the order of the nano to the micro and decrease the dielectric loss. The dielectric constant of CA-ZnONP/ITO and CA-ZnONR/ITO are respectively of 2569 and 97159 at 100 Hz. The capacitance and dielectric loss of CA-ZnONP/ITO and CA-ZnONR/ITO reach to 69.809 nF; 678 and 2,15765 ÂµF; 13,23 respectively.Â